2021
DOI: 10.1001/jamaophthalmol.2020.5114
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rhegmatogenous Retinal Detachment Incidence With Myopia Prevalence in the Netherlands

Abstract: IMPORTANCEThe incidence of rhegmatogenous retinal detachment (RRD) is partly determined by its risk factors, such as age, sex, cataract surgery, and myopia. Changes in the prevalence of these risk factors could change RRD incidence in the population. OBJECTIVE To determine whether the incidence of RRD in the Netherlands has changed over recent years and whether this change is associated with an altered prevalence of RRD risk factors. DESIGN, SETTING, AND PARTICIPANTSThis cohort study included data from all 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 31 publications
3
45
1
3
Order By: Relevance
“…Findings from this study were very consistent with a previous study by Kim and associates from a Korean population showing that the majority of younger individuals with RRD had high myopia compared with older individuals, determined by axial length of >26 mm. 3 Myopia has been strongly associated with RRD 1,4 due to the fact that myopic individuals, particularly those with high myopia, are more likely to have a thinner retina 5 and are prone to experience premature vitreous liquefactions causing posterior vitreous detachment. 6 Taken together, those factors are key for the development of retinal tear and subsequent RRD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from this study were very consistent with a previous study by Kim and associates from a Korean population showing that the majority of younger individuals with RRD had high myopia compared with older individuals, determined by axial length of >26 mm. 3 Myopia has been strongly associated with RRD 1,4 due to the fact that myopic individuals, particularly those with high myopia, are more likely to have a thinner retina 5 and are prone to experience premature vitreous liquefactions causing posterior vitreous detachment. 6 Taken together, those factors are key for the development of retinal tear and subsequent RRD.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia has been strongly associated with RRD 1 , 4 due to the fact that myopic individuals, particularly those with high myopia, are more likely to have a thinner retina 5 and are prone to experience premature vitreous liquefactions causing posterior vitreous detachment. 6 Taken together, those factors are key for the development of retinal tear and subsequent RRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An eye with a refractive error of more than −3 dioptres has a tenfold increased risk of RD compared to an emmetropic eye [ 9 ]. An analysis of the incidence of RRD in the Dutch consortium of hospitals to study a putative association of increasing RRD rates with myopia found it likely that higher rates of myopia in the population may explain part of the increase [ 16 ]. The increase in the number of performed cataract operations can be partly attributed to population aging, and hence a higher prevalence of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nielsen et al reported that the incidence of RRD is mainly increasing in the Caucasian population using the Danish National Patient Registry data from 2000 to 2016 [ 12 ] and suggested that the observed increase is primarily driven by male patients aged 50 years or older. Although not a nationwide cohort study, Redmer et al also reported an increase in primary RRD incidence in the Dutch population with a simultaneous myopic shift [ 13 ].…”
Section: Introductionmentioning
confidence: 99%